The use of communicative language teaching approach to improve english oral production skills - Solís Cervantes, Francisco Antonio (2022)
The present research work has as purpose to analyze the features and foundations of Communicative Language Teaching approach in young learners in English classrooms and to examine the effectiveness that this approach might have in oral production skills in Ecuadorian public high schools. Ecuador has been evidenced as a country with low English proficiency and this is mainly the response of several factors, such as the methodology that teachers use in class and the motivation students have in the foreign language.